Outcome of loop electrosurgical excision for HIV-positive women in a low-resource outpatient setting - Kietpeerakool C. (2014)
Objective: To assess outcome in HIV-positive women undergoing the loop electrosurgical excision procedure (LEEP). Method: A prospective study was conducted with 789 outpatients undergoing LEEP at Chiang Mai University Hospital between October 2004 and June 2008. Results: The 70 HIV-positive women (8.9%) were younger (P < 0.001) and had a lower parity (P < 0.001) than the remaining women. The proportion of women undergoing LEEP for persistent low-grade lesions was higher (8.6% vs 1.9%) and the prevalence of margin involvement was higher (60.0% vs 49.4%) among the HIV-positive women. After adjusting for age, parity, menopausal status, size of excised lesion, and histopathologic result, HIV infection was not significantly associated with LEEP complications (adjusted odds ratio, 0.41; 95% confidence interval, 0.15-1.15). Conclusion: The higher risk of resection margin involvement in HIV-infected women was not associated with LEEP complications. © 2008 Elsevier Ireland Ltd. All rights reserved.